The origin of phagocytosis in Earth history. Issue 4 (12th June 2020) - Mills, Daniel B.
Abstract : Phagocytosis, or 'cell eating', is a eukaryote-specific process where particulate matter is engulfed via invaginations of the plasma membrane. The origin of phagocytosis has been central to discussions on eukaryogenesis for decades, where it is argued as being either a prerequisite for, or consequence of, the acquisition of the ancestral mitochondrion. Recently, genomic and cytological evidence has increasingly supported the view that the pre-mitochondrial host cell—a bona fide archaeon branching within the 'Asgard' archaea—was incapable of phagocytosis and used alternative mechanisms to incorporate the alphaproteobacterial ancestor of mitochondria. Indeed, the diversity and variability of proteins associated with phagosomes across the eukaryotic tree suggest that phagocytosis, as seen in a variety of extant eukaryotes, may have evolved independently several times within the eukaryotic crown-group. Since phagocytosis is critical to the functioning of modern marine food webs (without it, there would be no microbial loop or animal life), multiple late origins of phagocytosis could help explain why many of the ecological and evolutionary innovations of the Neoproterozoic Era (e.g. the advent of eukaryotic biomineralization, the 'Rise of Algae' and the origin of animals) happened when they did.